PELAKSANAAN PERJANJIAN BAGI HASIL DI DESA KALIGLAGAH KECAMATAN LOANO KABUPATEN PURWOREJO - Kumalasari, Sulistyawati; Sigalingging, Hamonang; Suprayogi, Suprayogi (Unnes Civic Education Journal, 2015)
Community Kaliglagah use customary law on sharing agreements, a tradition that have been passed down through generations. This study aims at knowing the implementation of the agreements. The research method used was qualitative research methods. The research indicates that the implementation of agreements on production sharing agreements for the Village Kaliglagah is only based on an agreement between the owners of fields and tenants, a verbal agreement in nature, based on trust, without witnesses, and not done in the presence of the authority. The people use “maro” system for rice grown in paddy fields and “mertelu” for rice grown in non-paddy fields. Production costs for the system “maro” such as seed, fertilizer, and harvest wage rates are shared. Other costs are borne by farmers themselves. For mertelu system, the cost of production are borne by farmers except the expenses for fertilizer costs are shared harvest labor wages. Term of the agreement is not clear and unequivocal.